2015
DOI: 10.4187/respcare.03633
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Apnea-Hypopnea Index Measured by a Home Bi-Level Pressure Support Ventilator Versus a Polysomnographic Assessment

Abstract: BACKGROUND: Ventilators designed for home care provide clinicians with built-in software that records items such as compliance, leaks, average tidal volume, total ventilation, and indices of residual apnea and hypopnea. Recent studies have showed, however, an important variability between devices regarding reliability of data provided. In this study, we aimed to compare apneahypopnea indices (AHI) provided by home ventilators (AHI NIV ) versus data scored manually during polysomnography (AHI PSG ) in subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 26 publications
1
35
0
2
Order By: Relevance
“…A p value of <0.05 was considered significant. As only one recent cohort study [12] evaluated the reliability of events provided by the BIS as compared with PSG and it only included 10 patients, it was not possible to calculate a sample size on the basis of published data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A p value of <0.05 was considered significant. As only one recent cohort study [12] evaluated the reliability of events provided by the BIS as compared with PSG and it only included 10 patients, it was not possible to calculate a sample size on the basis of published data.…”
Section: Discussionmentioning
confidence: 99%
“…The interrater agreement of scoring respiratory events on both Reslink and PG between operators was determined by Cohen's kappa coefficient [15] . Recordings were dichotomously categorized as "normal" ( ≤ 10 events/hour) or "abnormal" (>10 events/hour) [12] . Differences between automatically and manually scored EI from both Reslink and PG were assessed using the Student t test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on stable subjects with obesity-hypoventilation syndrome, the BIS tested by the authors provided a reliable AHI compared to the PSG [73]. …”
Section: Modes and Monitoringmentioning
confidence: 99%
“…Recent studies have demonstrated their reliability and suggested their interest in clinical practice. [13][14][15] By providing an evaluation of ''critical signals'' involved in NIV effectiveness (i.e., arterial oxygen saturation, leaks, estimated minute ventilation and tidal volume) such systems provide very useful information for assessing quality of ventilation. 15 Some software systems allow a breath by breath evaluation of flow and pressure proposing raw signals close to those provided by PG/ PSG.…”
mentioning
confidence: 99%